Production of ROS and its effects on mitochondrial and nuclear DNA, human spermatozoa, and sperm function (Medical Journal of Indonesia, 2007)
Over the past few decades many researchers studying the causes of male infertility have recently focused on the role played by reactive oxygen species (ROS) â highly reactive oxidizing agents belonging to the class of free radicals. If ROS levels rise, oxidative stress (OS) occurs, which results in oxygen and oxygen derived oxidants, and in turn increases the rates of cellular damage. In human, ROS are produced by a variety of semen components, and antioxidants in the seminal fluid keep their level balance. Small amounts of ROS help spermatozoa acquire their necessary fertilizing capabilities. Many researches showed that ROS attack DNA integrity in the sperm nucleus by causing base modification, DNA strand breaks, and chromatin cross linking. The DNA damage induced excessive levels of ROS and might accelerate the process of germ cell apoptosis leading to a decline in sperm counts associated with male infertility. This paper will review the molecular (cellular) origins of ROS in human semen, how ROS damage sperm nuclear DNA, and how such DNA damage contributes to male infertility. Increased ROS production by spermatozoa is associated with a decreased mitochondrial membrane potential (MMP), which is an important indicator of functional integrity of the spermatozoa. Germ cell apoptosis is essential for normal spermatogenesis and its dysregulation may lead to male infertility. Thus, understanding the causes and mechanisms of germ cell apoptosis is of major importance in preventing male reproductive problems. Levels of apoptosis in mature spermatozoa that were significantly correlated with levels of seminal ROS determined by chemiluminescence assay indicate the linkage between ROS and male fertility problems. (Med J Indones 2007; 16:127-33) Keywords: Apoptosis, infertility, free radicals